Usability Analysis of Learning Device Monitoring Systems: Evaluation of User Experience for the Effectiveness of Educational Digitalization - Nurdin, Muhammad; Yahya, Muhammad; Nur, Hasanah (International Journal of Technology and Education Research, 2025)
This study aims to analyze the usability level of the learning tool monitoring system developed to support the digitalization of learning administration management in the educational environment. Usability is a crucial aspect in the successful implementation of the system, because it is directly related to the convenience, comfort, and effectiveness of use by teachers, supervisors, and education staff. This study uses a descriptive quantitative approach with evaluation instruments that refer to six usability characteristics, namely appropriateness recognizability, learnability, operability, user error protection, user interface aesthetics, and accessibility. Data was collected through the distribution of questionnaires to the respondents of the users of the system, and analyzed using descriptive statistics. The results of the analysis show that the system has an average usability value of 4.50 or 90.04%, which is classified as very good. The characteristics with the highest scores were accessibility (90.64%) and user interface aesthetics (90.42%), while the lowest scores were appropriateness recognizability (89.57%). These findings indicate that the system has met most of the users' expectations, especially in terms of the interface appearance, ease of access, and learning process of using the system. However, the aspects of function recognition and navigation still need to be slightly improved to be more optimal.